Bioremediation of shrimp pond wastewater using effective microorganism-4 (EM4) - Maysabila, Annisa; Heryanti, Rika; Permana, Rega; Hasan, Zahidah (Syiah Kuala University, 2023)
The problems of shrimp farming with semi-intensive systems are leftover feed, organic matter, and toxic compounds that can reduce water quality. Shrimp pond wastewater treatment can be done through several technologies, such as chemical, physical, and biological treatment. One of biological treatment that widely used for wastewater treatment is bioremediation. Bioremediation is a biological process that utilizes microorganisms to decompose waste in aquaculture ponds into compounds that are not harmful to aquatic biota. Therefore, this researchaims to determine the effect of effective microorganism-4 (EM4) in reducing ammonia compounds and BOD levels in shrimp pond wastewater. The research method used is a laboratory-scale experimental method. A total of6aquariums were used for 3 different treatments with two replications, control, adding EM4 2.5% and EM4 3% into 5 L of wastewater. Thewater quality parameters observed were dissolved oxygen, temperature, pH, ammonia, and BOD. Theone-wayANOVA test was used in this study. The results showed that there was a decrease in ammonia and BOD levels. The highest reduction of ammonia was found in the treatment with the addition of EM4 2.5%.The decrease in BOD with the highest effectiveness was found in the control treatment (37.73%)with the initial BOD value 5.3to3.3. mg/l, which fulfilled the allowed maximum level ofstandard of Ministerial Decree No. KKP. KEP.28/MEN/2004 concerning General Guidelines for Shrimp Cultivation in Ponds. In conclusion, the small dosage addition of EM4 did not have a significant effect on decreasing levels of ammonia and BOD.